Characteristics of heavy minerals and grain size of surface sediments on the continental shelf of Prydz Bay: implications for sediment provenance. Issue 2 (24th November 2015) - Wang, Haozhuang; Chen, Zhihua; Wang, Kunshan; Liu, Helin; Tang, Zheng; Huang, Yuanhui
Abstract: Data on grain size and heavy mineral composition for surface sediments on the Prydz Bay continental shelf was analysed to identify sediment features and provenance. The grain size composition of surface sediments indicate spatial variations in the glaciomarine environment and the key factors influencing sedimentation, which on the shelf include topography/water depth, currents and icebergs. The study area was divided into two sections by Q-type factor analysis: section I included Prydz Channel, Amery Basin and Svenner Channel, and section II included Four Ladies Bank, Fram Bank and the area in front of the Amery Ice Shelf. Sedimentation in section I is mainly controlled by currents and topography/water depth. However, in section II, icebergs/floating ice masses, the Amery Ice Shelf and currents have prominent effects on sedimentation. The heavy mineral composition indicates that surface sediments on the eastern side of the bay, including Four Ladies Bank, are primarily derived from Princess Elizabeth Land. Sediments in the area in front of the Amery Ice Shelf, Svenner Channel, Amery Basin and Prydz Channel have a mixed source from the eastern regions around the bay, including the Prince Charles Mountains and Princess Elizabeth Land. The contribution from Mac. Robertson Land to sediment at Fram Bank is limited.